The Effectiveness of Discovery Learning Model Assisted by Canva Media in Enhancing Critical Thinking Skills on The Topic of Preserving My Nation's Culture (A Quasi-Experimental Study in Grade VIII at SMP Negeri 3 Purbalingga) - Devika Indah Andiyani; Elly Hasan Sadeli; Wildan Nurul Fajar (UM Purwokerto Press, 2024)
This study aims to determine the influence of the discovery learning model assisted by Canva media in enhancing students’ critical thinking skill on preserving my nation’s culture at SMP negeri 3 Purbalingga. The method used in this study is quasi-experimental with nonequivalent control group design. The sample consisted of class VIII A as the experimental class (n=32) and VIII B as the control class (n=32). Data collection techniques used in this study were questionnaires, observation, and documentation, which were analyzed using paired sample tests and independent sample t-tests, yielding results of 0.000 0.05, indicating that the discovery learning model assisted by Canva media significantly enhances students' critical thinking skills. The experimental class showed an 81% improvement, while the control class showed a 75% improvement. This improvement was evidenced by the students' increased abilities in providing basic explanations, building basic skills, drawing conclusions, providing further explanations, using strategies or tactics, demonstrating curiosity, analyzing arguments, and solving problems with accurate sources.